Kajian Tasawuf Falsafi Mengenai Wahdat al-Wujud Ibn Arabi (1165-1243 M) - Indra Purnamanita, Eka Ismaya (TIN: Terapan Informatika Nusantara, 2023)
The study of philosophical Sufism should require deep appreciation and thought to study it so as not to fail to understand, because several figures of philosophical Sufism explain their thoughts through works written full of metaphors (figures of speech). Like Ibn Arabi, the concept of wahdat al-wujud, which is actually implied in his writings, especially Futuhat al-Makiyyah and Fushus al-Hikam, is said to be implied because the term wahdat al-wujud is not clearly stated. Wahdat al-wujud is interpreted as the unity of the universe with Allah SWT, but this unity is not complete or vice versa, the position of this unity still recognizes the transcendent superiority of Allah. In essence, only One exists, namely Allah, and its manifestation in the form of the universe is a picture of Allah's manifestation. In short, nothing that appears is eternal, because the only thing that is eternal and certain is One, namely Allah. Some thinkers say that this concept adapts and improvises previous Sufism thinkers, namely al-Hallaj with Hulul, then in western philosophy such as Plotinus with the One in emanation, and Permanindes with the Existing. The three dignities of Allah appear, namely ahadiyah, wahidiyah, and tajalli syuhudi. Each of these hierarchical dignities has its own way for God to appear.